Influence of Human Resource Management on Quality of Education in Public Primary Schools in Cameroon. (International Journal of Scientific Research and Management (IJSRM), 2022)
Most nations in the world are always in the process of national reconstruction. To consolidate this process, they have prioritised quality education as a bedrock of sustainable development. In this gruse, Cameroon like some African Countries have embarked on huge budgetary allocations in the education sector as well as the persuance of good governance geared toward the efficient and effective management of resources. This paper therefore aims at examining the role of efficient and effective human resource management in the promotion of quality education.This study is based on the prism that efficient and effective human resource management has a bearing on the quality of education. From the pratis of Human capital theory developed by Gary Stanley Becker(1960),this paper makes the postulation that the value of human capacities (knowledge, skills, intelligence, talents, experiences, behaviour, honesty, punctuality, competence and other attributes) could be developed through education and training so as to enhance productivity and thus quality of education.